The Use of Simulated Scenarios in the Training of the National Police: Pedagogical Innovation in SERÁS FORMACIÓN - Del Valle Mejías, María Elena (International Journal of Advanced Corporate Learning (iJAC), 2025)
Simulated scenarios have emerged as an effective pedagogical tool in the training of National Police officers, allowing trainees to develop critical skills in a controlled and realistic environment. This article explores the implementation of simulated scenarios in SERÁS FORMACIÓN, highlighting their theoretical basis, benefits and practical application. A specific example of a scenario related to domestic violence is presented, highlighting how these simulations contribute to the development of technical, emotional and ethical competencies essential in police performance.